SISTEM PENGELOLAAN PENGADUAN PELAYANAN PUBLIK NASIONAL–LAYANAN ASPIRASI DAN PENGADUAN ONLINE RAKYAT (SP4N-LAPOR) SEBAGAI MEDIA KOMUNIKASI ASPIRASI PUBLIK - Sy. Nurul Syobah; A. Rivai Beta; Linda Meilani; Mardiasih; Muhammad Alfiannur; Rajab; Rezqi Hutomo Achmad (STAI Nusantara Kota Banda Aceh, 2026)
The Community Service Program with the theme of utilizing SP4N-LAPOR as a medium for public aspiration communication aims to enhance the understanding and awareness of students at Universitas Muhammadiyah Kalimantan Timur (UMKT) Samarinda regarding effective, participatory, and ethical public communication. This activity was implemented through an educational and participatory approach using material presentations and interactive discussions, in collaboration with the Department of Communication and Informatics of East Kalimantan Province. The materials presented included an introduction to SP4N-LAPOR, two- way communication, public communication ethics, and community participation in monitoring public services. The results indicate an improvement in students’ understanding of the function of SP4N-LAPOR as an official communication channel between the public and the government, as well as increased awareness of the importance of message clarity and ethical considerations in conveying public aspirations. This activity has a positive impact on enhancing students’ public communication literacy in the digital era.